2015
DOI: 10.1371/journal.pone.0132742
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Genetics Content in the Next Generation Science Standards

Abstract: Science standards have a long history in the United States and currently form the backbone of efforts to improve primary and secondary education in science, technology, engineering, and math (STEM). Although there has been much political controversy over the influence of standards on teacher autonomy and student performance, little light has been shed on how well standards cover science content. We assessed the coverage of genetics content in the Next Generation Science Standards (NGSS) using a consensus list … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…In recent years, access to pharmacogenomics, nutrigenomics, disease risk, ancestry and ethnicity tests, as well as access to sport genetic analyses, has become widespread in low- and middle-income countries. Such genetic and genomic practices are carried out by health care institutions and, moreover, direct-to-consumer (DTC) genetic tests are easily available on the internet ( Covolo et al , 2015; Phillips, 2016). In Ecuador, a case study by the Red Cross found that rape, intimate partner violence and femicide rates are high.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, access to pharmacogenomics, nutrigenomics, disease risk, ancestry and ethnicity tests, as well as access to sport genetic analyses, has become widespread in low- and middle-income countries. Such genetic and genomic practices are carried out by health care institutions and, moreover, direct-to-consumer (DTC) genetic tests are easily available on the internet ( Covolo et al , 2015; Phillips, 2016). In Ecuador, a case study by the Red Cross found that rape, intimate partner violence and femicide rates are high.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to ELA and mathematics, making adequate yearly progress (AYP) toward proficiency on high-stakes assessments was not mandated in science (NCLB, 2002;Lontok, Zhang, Dougherty, 2015).…”
Section: How Did We Get Here?mentioning
confidence: 99%
“…The idea of genetic data is popular among non-scientists, but its understanding and consequences are poorly understood. Coverage of core genetic concepts in science, technology, engineering, and math (STEM) education is highly variable (Dougherty et al 2011;Lontok et al 2015) and genetic literacy is persistently low among the United States (US) general population (Haga et al 2013). Despite the technical chasm, persistent pop cultural references to genetics and genomics in both entertainment and the media have elevated and maintained the voguishness of these data.…”
Section: Genetics Is Mainstreammentioning
confidence: 99%